Sentence Context Prevails Over Word Association in Aphasia Patients with Spared Comprehension: Evidence from N400 Event-Related Potential - Khachatryan, Elvira; De Letter, Miet; Vanhoof, Gertie; Goeleven, Ann; Van Hulle, Marc M. (Frontiers in Human Neuroscience, 2017)
Behavioral and event related potential (ERP) studies on aphasia patients showed that lexical information is not lost but rather its integration into the working context is hampered. Studies have been conducted on the processing of sentence-level information (meaningful versus meaningless) and of word-level information (related versus unrelated) in aphasia patients, but we are not aware of any study that assesses the relationship between the two. In healthy subjects the processing of a single word in a sentence context has been studied using the N400 ERP. It was shown that, even when there is only a weak expectation of a final word in a sentence, this expectation will dominate word relatedness. In order to study the effect of semantic relatedness between words in sentence processing in aphasia patients, we conducted a crossed-design ERP study, crossing the factors of word relatedness and sentence congruity. We tested aphasia patients with mild to minimum comprehension deficit and healthy young and older (age-matched with our patients) controls on a semantic anomaly judgment task when simultaneously recording EEG. Our results show that our aphasia patient’s N400 amplitudes in response to the sentences of our crossed-design study were similar to those of our age-matched healthy subjects. However, we detected an increase in the N400 ERP latency in those patients, indicating a delay in the integration of the new word into the working context. Additionally, we observed a positive correlation between comprehension level of those patients and N400 effect in response to meaningful sentences without word relatedness contrasted to meaningless sentences without word relatedness.